The Effects of a 3-Week Heartbeat Perception Training on Interoceptive Abilities - Schillings, Christine; Karanassios, Georgios; Schulte, Niklas; Schultchen, Dana; Pollatos, Olga (Frontiers in Neuroscience, 2022)
Recent studies showed promising short-term effects of heartbeat perception training on interoceptive abilities. Research on the effects of heartbeat perception training on interoceptive abilities over time is sparse. Therefore, the aim of the study was to examine short-term effects and the effects of a three-week heartbeat perception training over time on interoceptive abilities, namely, cardiac interoceptive accuracy (IAc) and interoceptive sensibility (IS). Fourty healthy participants were randomized to the intervention group (n = 20) or the control group (n = 20). The intervention group conducted three cardiac biofeedback sessions (one per week) at the laboratory, whereas the control group watched a documentary instead. Interoceptive abilities were assessed via the heartbeat perception task (IAc) and confidence ratings (IS) at baseline, after each laboratory session, and one week after the last session (post-measurement). IAc was significantly increased in the intervention group compared to the control group after the first training session (short-term effect). There were no significant improvements in IS due to the first session, and neither on IAc nor IS over time. Descriptive trends of improved interoceptive abilities over time was found in both groups. Single sessions of heartbeat perception training seem to be a promising approach to improve IAc. Future research should further investigate the long-term effects of diverse heartbeat perception training varying in frequency and intensity of the training sessions in diverse samples aiming to improve interoceptive abilities.